UNESCO Gastronomi Şehri Olmada Paydaş Farkındalığı: Kastamonu Örneği - ÖZDEMİR, Osman; AYDOĞDU, Aydoğan (Isparta University of Applied Sciences, 2021)
In the study, Kastamonu's application to the Unesco Creative Cities Network as a gastronomy city and the awareness of stakeholders regarding this application were tried to be understood. In this context, the tourism situation of Kastamonu and the knowledge and interest of stakeholders on the subject were investigated. Participants authorized in the field of tourism from the governorship, municipality, provincial culture and tourism directorate, development agency, private sector, university, NGOs constitute the sample of the research. A qualitative research was carried out by holding 45-minute in-depth interviews with the participants. As a result, it has been observed that the stakeholders who did not take an active role in the process were more hopeful about the result of Kastamonu being a gastronomy city. The study is expected to benefit managers and academics.

Kastamonu’nun gastronomi şehri olarak Unesco Yaratıcı Şehirler Ağı’na başvurusu; paydaşların bu başvuruya yönelik farkındalığı anlaşılmaya çalışılmıştır. Bu bağlamda Kastamonu’nun turizm durumu; paydaşların konu hakkındaki bilgisi ve ilgisi araştırılmıştır. Valilik, belediye, il kültür ve turizm müdürlüğü, kalkınma ajansı, özel sektör, üniversite, STK’lardan turizm alanında yetkili katılımcılar araştırmanın örneklemini oluşturmakta olup katılımcılar ile 45’er dakikalık derinlemesine mülakatlar gerçekleştirilerek nitel bir araştırma gerçekleştirilmiştir. Sonuç olarak, süreç içerisinde aktif rol almayan paydaşların Kastamonu’nun gastronomi şehri olması konusunda, sonuçtan daha umutlu olduğu görülmüş olup çalışmanın yöneticilere ve akademisyenlere fayda sağlanması beklenmektedir.
Keywords: Kastamonu; UNESCO; Turizm (Diğer); Gastronomi; Tourism (Other); Unesco; Creative Cities Network; Gastronomy; Kastamonu; Yaratıcı Şehirler Ağı; Unesco; Yaratıcı Şehirler Ağı; Gastronomi; 4. Education; 11. Sustainability; 16. Peace & justice